Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey - Döker, İsmai̇l; Kazak, Cengi̇z; Karut, Kami̇l (Zootaxa, 2017)
Three new species of the family Phytoseiidae (Acari: Mesostigmata) are described and illustrated based on female specimens collected from various plants in Turkey—Eharius denizliensis Döker & Kazak sp. nov., Typhlodromus (Anthoseius) karaisaliensis Döker & Kazak sp. nov. and Typhlodromus (Typhlodromus) papadoulisi Döker & Kazak sp. nov.